EFFECTIVE AGROTECHNOLOGY FOR GROWING PEACH SEEDLINGS IN FOG-GENERATING STRUCTURES - Khatamova Hamidakhan Komiljonovna (Web of Journals Publishing, 2025)
The issue of improving the health of the population, increasing the popularity of food products, primarily natural products rich in vitamins and medicinals, especially fruits, is considered one of the most important issues around the world. In this regard, the peach fruit is of special importance with its unique taste and composition. According to the UN Food and Agriculture Organization, 24.7 million people worldwide eat about tons of peaches are grown, "China is the leader in peach cultivation and there are 15.00 million tons of peaches are harvested. Also, countries such as Spain (13.06 million tons), Italy (10.15 million tons), Turkey (892 thousand tons), Greece (890.6 thousand tons), Iran (663.6 thousand tons) produce peaches. It is one of the leading countries in terms of production. Mechanization and intensification of agro-technological processes, from the cultivation of peach seedlings to harvesting, to ensure the continuous consumption of peaches by the world's population, to ensure the continuity of its cultivation is an urgent task.
Keywords: Peaches, pen, intensive, tumanka, seedling, agrotechnics, temperature, crop, grain, new varieties.